Role of Geographical Factors in the Evolution and Growth of the Military System of the Delhi Sultanate: The Influence of Geographical Factors on the Military System of the Delhi Sultanate (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The geographical factors played an important role in the evolution and growth of the military system of the Delhi Sultanate. These factors include the plains, mountains, hills, forests, deserts, rivers, climate, sea and routes.